MEN, MASCULINITIES AND GENDER POLITICS IN SOUTH AFRICA: A REPLY TO MACLEOD - Morrell, Robert (PINS-Psychology in Society, 2025)
The last decade has seen a growth in academic work on men and masculinity in Southern Africa. Inspired by a global trend, local studies have extended their range, empirical depth and analytical sophistication. The major consequence of this turn to the study of masculinities and men has been an enhanced understanding of gender relations in Southern Africa.